2017
DOI: 10.1590/2177-9465-ean-2016-0380
|View full text |Cite
|
Sign up to set email alerts
|

Work of family health strategy nurses in oncology care

Abstract: Objective: To identify the qualification of and to know the work of Family Health Strategy nurses in oncology care. Methods: A cross-sectional, descriptive study, using a quantitative approach, was conducted with 77 nurses working in the Family Health Strategy units of Campo Grande, state of Mato Grosso do Sul. Primary data were collected in structured interviews, using a form with closed-ended questions. Results: Professional training in oncology care is less frequent, reflecting a high lack of knowledge rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
6
0
7
Order By: Relevance
“…The training of generalist nurses has provided discussions regarding curricular plans that train professionals to act in the country's health situation (24) . Souza, Cazola e Oliveira (25) conducted a study to know the nurses' situation in the Family Health Strategy program that cares cancer patients in the city of Campo Grande, State of Minas Gerais. Results showed that 78% of the nurses interviewed had patients with cancer in their care area, and 95% of those nurses monitored cancer patients (25) .…”
Section: Discussionmentioning
confidence: 99%
“…The training of generalist nurses has provided discussions regarding curricular plans that train professionals to act in the country's health situation (24) . Souza, Cazola e Oliveira (25) conducted a study to know the nurses' situation in the Family Health Strategy program that cares cancer patients in the city of Campo Grande, State of Minas Gerais. Results showed that 78% of the nurses interviewed had patients with cancer in their care area, and 95% of those nurses monitored cancer patients (25) .…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, the Ministry of Health implemented the National Oncological Care Plan (PNAO) which aims to implement everything from health promotion to palliative care 15 . In a study carried out in Campo Grande (MS), most primary care nurses were unaware of this plan, which greatly implies supporting the population's health 20 . So, in Brazil (2011), the Federal Court of Auditors 22 presented an audit report and found that the care network was unable to provide equal access to the services present in PNAC.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing education for all professionals, regardless of the level of care, within the scope of health promotion, expands the autonomy of these professionals, improving the quality of cancer care. 12 Trained professionals can instigate and empower people's self-knowledge and self-care at the individual and collective level, through the groups, which may contribute to the early detection of the disease, timely treatment and increase in the disease survival rate.…”
Section: Training On This For Health Professionals (Giennah) Training Of Employees Jointly Between Basic and Specialized Care (Zaniah)mentioning
confidence: 99%